Agriculture: Is climate change a serious issue? - Cruse, Richard M. (Agrociencia Uruguay, 2012)
A changing climate coupled with rapidly increasing demand for agricultural products will offer challenges greater than any previously experienced by global agriculture. The changing above ground environment, including air temperature, precipitation and carbon dioxide concentrations, will impact crops directly as these factors impact plant physiologic processes. Less well recognized is that for world agricultural demands to be met, vast increases of nutrients and water must be supplied to crop plants from soils in which they grow. This must occur while expansive areas of currently farmed soils are being degraded, projected increased frequency of climate extremes will intensify current soil degradation pressure, and aquifer stress is limiting production in important grain producing areas. Expansion of agriculture into currently unfarmed areas could improve global food security; however continued conversion of agricultural land to other more economically viable uses will act to counterbalance agriculture’s spatial expansion. The soil scientist challenge to help maintain soil productivity on soil less suitable for crop production in the face of increasing crop production demands will require imagination, innovation, and investment greater than currently occurring.